Personal files of clergymen in diocesan repositories as a source on the history of the Russian Orthodox Church in the middle — second half of the 20th century (using materials of Smolensk diocesan administration) - Ilya Burdukov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2022)
This article is devoted to the study of one of the least studied groups of historical sources - the personal files of clergy. The archive of the Smolensk diocesan administration was used as a representative material. Based on the causal method, it was possible to consider a number of personal affairs of clergymen and, on their basis, identify those thematic blocks, the study of which contributes to a fuller and deeper immersion in the historical realities of the existence of the Russian Orthodox Church through the prism of the life and work of the clergy. The documents of the diocesan archives are able to shed light on certain circumstances of the life of a clergyman of the Soviet period and see his true portrait thanks to the testimonies that have been preserved in personal files - service records, autobiographies, complaints, clippings from periodicals, etc. The determining factor in the objectivity of consideration of this kind of documents involves the use of an integrated approach that can fill those gaps that are inevitable in office work. In this regard, when studying the personal files of clergymen of the Soviet period, it is necessary to take into account the factor of verification of the information contained in them due to political realities and the subjectivity of decisions of one bishop or another, or employees of the diocesan administration. This work does not claim to be exhausted. On the contrary, this attempt at research is aimed, firstly, at drawing attention to the problem of the lack of knowledge of the designated kind of sources. Secondly, it seems important to pay attention to the safety and accessibility for researchers of diocesan archives. The latter requires special attention, and the fate of a significant layer of history not only of the Church, its ministers, but also of our state depends on the resolution of these issues